PENERAPAN BERMAIN KASVO UNTUK MENINGKATKAN HASIL BELAJAR SERVIS BAWAH BOLA VOLI PADA SISWA KELAS IV SD NEGERI 1 PADAS KABUPATEN GROBOGAN TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the level of success through volleyballunder serve application kasvo game in fourth grade student of Padas 1 state elementaryschool Grobogan regency Academic Year 2012/2013. This research is aclassroom action research was conducted in two cycles, in each cycle consisting of fourstages: planning phase, implementation phase, Observation phase and Reflec-tionphase. The subjects in this study are all fourth grade students of Padas 1 stateelementary school district Kedungjati Grobogan regency totaling 18 students, consistingof 4 sons and 14 daughters. Data analysis technique used is the percentage ofservice and instrument down on the game kasvo. From the results of the study in thefirst cycle of the material aspects of koqnitif reached 83%, 87% affective aspect , 77%psychomotor aspects, but the mastery learning students only reached 66.66% only. Sostated that in the first cycle of learning has not been successful. While in the secondcycle of achievement aspect koqnitif reached 88%, reaching 87% afektiff aspect,psychomotor aspect reaches 79%, the percentage of student mastery have reached 89%.With the attainment of class classical completeness criteria of 85% then that action canbe taken that Kasvo Application to Improve Learning result of Volleyball under ServeIn Fourth Grade Students of Padas 1 state elementary school Grobogan regencyAcademic Year 2012/2013 can be declared a success.